2015
DOI: 10.3390/rs70404318
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Case-Based Reasoning Approach for Landslide Detection: Integration of Object-Oriented Image Analysis and a Genetic Algorithm

Abstract: This paper proposes an automatic method for detecting landslides by using an integrated approach comprising object-oriented image analysis (OOIA), a genetic algorithm (GA), and a case-based reasoning (CBR) technique. It consists of three main phases: (1) image processing and multi-image segmentation; (2) feature optimization; and (3) detecting landslides. The proposed approach was employed in a fast-growing urban region, the Pearl River Delta in South China. The results of detection were validated with the hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 39 publications
1
77
0
2
Order By: Relevance
“…For this reason, our research also constitutes a novel approach for solving the calibration of complex models in remote sensing by reducing uncertainties through parametrization. This method is different from other optimization approaches in remote sensing, where the principal application is classification and pattern recognition [8][9][10]; however, it is closer to the approach of Reference [15] for calibrating a model of cellular automata.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, our research also constitutes a novel approach for solving the calibration of complex models in remote sensing by reducing uncertainties through parametrization. This method is different from other optimization approaches in remote sensing, where the principal application is classification and pattern recognition [8][9][10]; however, it is closer to the approach of Reference [15] for calibrating a model of cellular automata.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, optimization has been shown to be successful in remote sensing. Examples vary according to the field and the search algorithm applied [8][9][10]. Genetic algorithms (GAs) have a long history of refinement since it became popular though the work of Holland [11]; extensive research has reported it as a robust and efficient optimization algorithm with a wide range of application in areas such as engineering, numerical optimization, robotics, classification, pattern recognition, and product design, among others [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned methods are less effective than Light Detection and Ranging (LiDAR) at detecting large landslides that have experienced significant historical activity [33]. The use of LiDAR technology for landslide identification has become increasingly popular in digital terrain modelling [12,[34][35][36][37][38][39][40]. LiDAR is a valuable tool in geology [41], geomorphology [12], and hazard reduction efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The most common data mining methods used in landslide modeling are artificial neural networks [11,15,16], support vector machines [17][18][19][20][21], decision trees [10,20,22], and neuro-fuzzy [23,24]. Literature review shows that new data mining algorithms are suitable for landslide modeling for large and complex areas with good results [3,[25][26][27][28][29][30], and, in general, data mining models outperform conventional methods [10,[31][32][33]. However, recent studies on landslide modeling show that the overall performance of prediction models could be enhanced with the use of ensemble frameworks [31,34,35].…”
Section: Introductionmentioning
confidence: 99%